Exploring Employability Competencies in Construction Trades: A Comparative Analysis of Bricklaying/Block Laying and Concreting Graduates in Diverse Specializations in Gombe State, Nigeria - V., Apagu, V.; A., Baba; T., Abba, A. (Darul Yasin Al Sys, 2024)
The purpose of this study was to Explore the Employability Competencies in Construction Trades: A Comparative Analysis of Bricklaying/Block Laying and Concreting Graduates in Diverse Specializations in Gombe State, Nigeria. The study was guided by three research questions and three null hypotheses guided the study. The study's population comprised 85 respondents, including 21 administrators, 48 teachers, and 16 building supervisors, making sampling unnecessary due to the manageable size of the population. Data collection utilized a structured questionnaire titled